DIRECTIONS OF DIVERSIFYING INNOVATION PROCESSES IN THE INDUSTRY NETWORK (World Economics and Finance Bulletin, 2022)
The article develops an approach to innovation processes in industrial production from the point of view of diversification. Priority directions for diversification of production of new products are indicated. This process was viewed from the point of view of the implementation of fundamental structural reforms in the economy, subject to the state's strategic, innovative and economic goals. The socio-economic importance of management of diversification processes in the industrial network is appreciated
Keywords: develops; industrial; point; diversification